Anthropometric, gait and strength characteristics of Kenyan distance runners - Kong, P. W.; de Heer, H. (Journal of Sports Science & Medicine, 2008)
This study intended to take a biomechanical approach to understand the success of Kenyan distance runners. Anthropometric, gait and lower extremity strength characteristics of six elite Kenyan distance runners were analyzed. Stride frequency, relative stride length and ground contact time were measured at five running speeds (3.5 - 5.4 m/s) using a motion capture system. Isometric knee extension and flexion torques were measured at six angles and hamstrings and quadriceps (H:Q) ratios at three angular velocities were determined using an isokinetic dynamometer. These runners were characterized by a low body mass index (20.1 ± 1.8 kg·m- 2), low percentage body fat (5.1 ± 1.6%) and small calf circumference (34.5 ± 2.3 cm). At all running speeds, the ground contact time was shorter (p < 0.05) during right (170 - 212 ms) compared to left (177 - 220 ms) foot contacts. No bilateral difference was observed in other gait or strength variables. Their maximal isometric strength was lower than other runners (knee extension: 1.4 - 2.6 Nm·kg-1, knee flexion: 1.0 - 1.4 Nm·kg-1) but their H:Q ratios were higher than athletes in other sports (1.03 ± 0.51 at 60o/s, 1.44 ± 0.46 at 120o/s, 1.59 ± 0.66 at 180o/s). The slim limbs of Kenyan distance runners may positively contribute to performance by having a low moment of inertia and thus requiring less muscular effort in leg swing. The short ground contact time observed may be related to good running economy since there is less time for the braking force to decelerate forward motion of the body. These runners displayed minor gait asymmetry, though the difference may be too small to be practically significant. Further investigations are needed to confirm whether the bilateral symmetry in strength and high H:Q ratios are related to genetics, training or the lack of injuries in these runners.